KNOWLEDGE TRANSFER IN INNOVATION: IMPACT, TRENDS AND RELEVANT STRATEGIES IN THE SOCIAL AND ECONOMIC SECTORS OF LATIN AMERICA - Rincón Soto, Idana Beroska (2025)
Objective: To analyze innovation trends in Latin America, identifying structural challenges and strategies to strengthen the innovation ecosystem in the region, with special emphasis on investment in R+D, entrepreneurship and intersectoral collaboration. Methodology: A comparative analysis of the innovation scores of Latin American countries in the GII 2023 was conducted. Variables such as investment in science and technology, policies to support startups, digital infrastructure and collaboration between the public and private sectors were considered. Results: A gap in innovation was evident between the countries analyzed. Brazil and Chile stand out for their advances in R+D and technological entrepreneurship, while Mexico, Argentina and Colombia require greater investment and strategic policies. Costa Rica has demonstrated progress in education and digital infrastructure, consolidating itself as a benchmark in sustainable innovation in the region. However, challenges remain in technology transfer and in the effective linkage between universities and industry. Conclusions: Latin America needs to strengthen its innovation ecosystem through policies of investment in applied research, promotion of technological entrepreneurship and improvement of digital infrastructure. Collaboration between universities, governments and companies is key to closing the gap with more advanced economies. In addition, knowledge transfer should be enhanced with tax incentives and regional cooperation networks. The case of Costa Rica demonstrates that sustainable strategies can generate significant progress, serving as a model for other emerging economies.